2012
DOI: 10.1097/igc.0b013e3182481611
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function After Intracavitary Vaginal Brachytherapy for Early-Stage Endometrial Carcinoma

Abstract: Objective To describe the effects of intracavitary brachytherapy (IVB) on sexual function and quality of life of women with early-stage endometrial cancer. Methods Women with International Federation of Gynecology and Obstetrics stage I to stage II endometrial cancer treated surgically with or without IVB were identified and mailed questionnaires. Quality of life and sexual function were measured using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
1
15
0
4
Order By: Relevance
“…From the quality-of-life analysis of the PORTEC-2 study, it was reported that only 15% of the women were sexually active at baseline and no difference was noted for external beam therapy and vaginal brachytherapy with regard to sexual functioning and symptoms. 20 In a study by Quick et al, 22 the outcome on sexual function was similar after adjuvant vaginal brachytherapy and surgery alone. In future studies on quality-of-life in endometrial carcinoma, the new EORTC QLQ-EN24 cancer module should be used.…”
Section: Discussionmentioning
confidence: 93%
“…From the quality-of-life analysis of the PORTEC-2 study, it was reported that only 15% of the women were sexually active at baseline and no difference was noted for external beam therapy and vaginal brachytherapy with regard to sexual functioning and symptoms. 20 In a study by Quick et al, 22 the outcome on sexual function was similar after adjuvant vaginal brachytherapy and surgery alone. In future studies on quality-of-life in endometrial carcinoma, the new EORTC QLQ-EN24 cancer module should be used.…”
Section: Discussionmentioning
confidence: 93%
“…Patients with rectal cancer who needed postoperative chemotherapy were less likely to adhere, most likely due to treatment-related side effects, such as bowel dysfunction, fatigue, and neutropenia related to surgery and adjuvant chemotherapy. Their longer treatment course [24] with more acute side effects may have lessened the priority of long-term health maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Several small cross-sectional studies have not shown a difference in sexual function in endometrial patients undergoing hysterectomy and VBT compared to women who received hysterectomy alone [20, 21] or compared to a healthy postmenopausal control [22]. Nonetheless, Quick et al showed that compared to before the diagnosis of cancer, the majority of patients felt their vagina was smaller and reported increased vaginal dryness, more pain with intercourse, and less interest in sex [21].…”
Section: Impact Of Gynecologic Cancer On Sexual Healthmentioning
confidence: 99%
“…Nonetheless, Quick et al showed that compared to before the diagnosis of cancer, the majority of patients felt their vagina was smaller and reported increased vaginal dryness, more pain with intercourse, and less interest in sex [21]. In a study by Damast et al, 81% of patients who underwent hysterectomy with adjuvant VBT reported sexual dysfunction.…”
Section: Impact Of Gynecologic Cancer On Sexual Healthmentioning
confidence: 99%